2012
DOI: 10.1111/j.1600-0447.2012.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety as a marker of severity in acute mania

Abstract: An association of anxiety symptoms with greater severity in acute mania was demonstrated. The close relationship between anxiety and manic symptoms highlights the need for greater clinical attention to anxiety in this population. Further studies are necessary to determine whether effective treatment of anxiety symptoms could improve clinical and care outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…Anxiety has also been related to more severe illness in another study, having important consequences regarding symptom-rated and patient-rated outcomes 73–75. An association of the presence of anxiety symptoms with greater severity of manic symptoms and longer hospitalisations was demonstrated 76. Patients can experience work, family, social impairment and increased healthcare costs and strains on family support 73.…”
Section: Discussionmentioning
confidence: 98%
“…Anxiety has also been related to more severe illness in another study, having important consequences regarding symptom-rated and patient-rated outcomes 73–75. An association of the presence of anxiety symptoms with greater severity of manic symptoms and longer hospitalisations was demonstrated 76. Patients can experience work, family, social impairment and increased healthcare costs and strains on family support 73.…”
Section: Discussionmentioning
confidence: 98%
“…Previous empirical findings examining the association between anxiety comorbidity and mania/hypomania have been equivocal. González-Pinto and colleagues (2012) demonstrated that among bipolar I inpatients, anxiety symptoms were associated with exacerbated manic symptoms. Conversely, Saunders and colleagues (2012) found no significant relationship between anxiety and severity/number of manic episodes; Magalhães and colleagues (2010) reported no association between the presence of OCD and manic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of anxiety frequently co‐occur during a manic episode, and are a predictor of poor outcome; including greater severity of manic symptoms,197 a longer time to remission,197, 198 and more reported side effects of medication 198. There have been no studies specifically examining the efficacy of any agents in reducing symptoms of anxiety during a manic episode, although these symptoms do tend to improve concurrently with mood disturbance.…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%